EVALUASI PENJAMINAN MUTU PENDIDIKAN AGAMA ISLAM DAN IMPLIKASINYA PADA PRESTASI LEMBAGA PENDIDIKAN: (Studi di Sekolah Menengah Pertama Islam Terpadu AL Qalam) - Aris Try Andreas Putra; Erni Qomariyah (Halu Oleo University, 2024)
The evaluation of the quality assurance system at SMPIT AL Qalam using the CIPP model indicates success in the implementation of Islamic education. Challenges in curriculum adaptation and teaching methodology were identified as areas requiring further attention. Meanwhile, investments in human resource development and the implementation of active learning strategies have contributed to improved student understanding. The evaluation results reflect encouraging achievements, showing solid academic growth and character building in accordance with Islamic values, which confirms the quality of education provided by SMPIT AL Qalam.